2016
DOI: 10.4236/ijcm.2016.71005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Hydrogen Administration: From Animal and Human Diseases to Exercise Medicine

Abstract: Here we review the literature on the effects of molecular hydrogen (H2) on normal human subjects and patients with a variety of diagnoses, such as metabolic, rheumatic, cardiovascular and neurodegenerative and other diseases, infections and physical and radiation damage as well as effects on aging and exercise. Although the effects of H2 have been studied in multiple animal models of human disease, such studies will not be reviewed in depth here. H2 can be administered as a gas, in saline implants or infusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 310 publications
(468 reference statements)
0
60
0
3
Order By: Relevance
“…Molecular hydrogen has been shown to be useful in the treatment of various medical conditions and as an antiaging supplement [22,23]. Here we examined the effects of a commercial source of hydrogenized water on cultured human brain cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular hydrogen has been shown to be useful in the treatment of various medical conditions and as an antiaging supplement [22,23]. Here we examined the effects of a commercial source of hydrogenized water on cultured human brain cells.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenized water has been shown to act as a cellular antioxidant and gene regulator [22,23]. Previously we found that hydrogenized water was an effective cellular antioxidant and could decrease transport of glucose in a dose-and time-dependent manner and elevate the levels of phosphorylation of Akt, a protein kinase B biomarker for insulin signaling [24].…”
Section: Introductionmentioning
confidence: 99%
“…A very safe and effective method to control oxidative stress and reduce inflammation during mycoplasma treatment is the use of hydrogenized water [160]. Molecular hydrogen reduces oxidative stress and cytotoxic oxygen radicals by a gene regulation mechanism not by direct interactions [161].…”
Section: Modifying Mycoplasma Microenvironmentsmentioning
confidence: 99%
“…Hydrogenized water does not interfere with conventional or integrative therapies against mycoplasmas. It can be easily consumed orally without need to worry about contraindications [160].…”
Section: Modifying Mycoplasma Microenvironmentsmentioning
confidence: 99%
“…It has also been demonstrated that H 2 rapidly diffuses across cell membranes and is an effective ·OH radical scavenger in cultured cells and this has been related to its ability to rapidly diffuse across cell membranes. Since then, numerous studies have focused on understanding the potential therapeutic value of hydrogen and hydrogen-rich water in various disease models [12,13].…”
Section: Introductionmentioning
confidence: 99%